Development Of An Evidence-Based Checklist For The Detection Of Drug-Related Problems (Drps) Among Patients With Allergy Symptoms In Community Pharmacies - Appalasamy, Jamuna Rani (2013)
Pharmacists in community practice is making many improvements in the quality and safety of patients especially in detecting drug related problems (DRP) related to pharmaceutical care. The objective of this study was to develop a checklist which would be able to detect drug related problems among patients with allergy symptoms who seek treatment in community pharmacies. This study also aimed to detect types of DRPs and its prevalence.The Checklist Development Phase involved review of literatures. The developed checklist was then tested in validation phase where it was used in a community setting to obtain data and to get it validated. Four expert panel agreement, predictive values, sensitivity and specificity tests were done to validate the checklist. This validated checklist was then field-tested in two groups (Group 1; with the checklist) and (Group 2; without checklist).During the validation phase, 378 patients were interviewed.